Efektifitas Pemberian Dispensasi Kawin Pada Anak Di Bawah Umur Menurut Undang-undang No.1 Tahun 1974 (Studi Kasus Di Kab. Polewali Mandar) - Ade Rahayu (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
Marriage dispensation is the relief of something (age limit) in bonding between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the One Godhead. The purpose of this study was to determine and analyze the effectiveness of Marriage Dispensation in Underage Children in Polewali Mandar Regency and the factors that influence the judge's decision to grant the request for mating dispensation in minors in Polewali Mandar district. The research method used is empirical legal research. The results showed that underage marriage in Polewali Mandar district had not been implemented effectively because underage marriage was still found without going through mating dispensation and the factors that influenced the judge's decision to grant the request were because the prospective bride had been pregnant out of wedlock. Because the judge is not bound by positive law so the judge is given the opportunity to find the law. The judge prioritizes the concept of maslahah mursalah, where the judge chooses consideration of goodness and rejects damage in society and prevents harm.